Assessing the Impact and Challenges in Contemporary World Politics: A Case Study on Pakistani International and Global Peace - Muhammad, Imran (2024)
This thesis investigates the role of international law in maintaining global peace, with a specific focus on the United Nations (UN) as the primary mechanism through which international law is implemented. The central argument is that international law, predominantly through the UN's framework, plays a crucial role in sustaining global peace, despite various contemporary challenges that impede its full effectiveness. The research explores the intricate relationship between international law, peace, and security, seeking to determine whether global peace is a direct result of the implementation of international laws through the UN's legal system or if other factors contribute to this outcome. The objective is to critically assess whether international law alone is responsible for global peace or if other elements, such as geopolitical interests and power dynamics, also play significant roles. Employing a qualitative research methodology, the study relies on content analysis of relevant documents and treaties. This approach systematically analyzes textual data to uncover patterns, themes, and meanings related to the role of international law in peacekeeping. The research design is rooted in qualitative content analysis, which provides a nuanced understanding of how international law influences global peace. Thesis delves into the effectiveness of the UN Charter, alongside other international treaties, in maintaining peace. It examines the UN's role in key conflict zones, particularly in the Middle East and South Asia, with a focus on the Palestine-Israel conflict, the Iran-Iraq War, the Kuwait-Iraq War, and the Kashmir issue. In the Middle East, the UN's interventions in the Palestine-Israel conflict, the Iran-Iraq War, and the Kuwait-Iraq War highlight its capacity to mediate and attempt to resolve disputes. However, the research also acknowledges the challenges which the UN faces in enforcing its resolutions and maintaining peace in these regions. For instance, while the UN played a pivotal role in ending the Kuwait-Iraq War through swift and decisive action, its efforts in resolving the Palestine issue have been less successful, despite numerous attempts to mediate peace. Also, UN spent eight years to stop the war between Iraq and Iran. And in its involvement in South Asia, particularly in the Kashmir issue, the UN had recommended a plebiscite to determine the region's future. The study concludes that international law, through the UN, is indeed a central mechanism for maintaining global peace but its effectiveness is often hampered by challenges in enforcement and the influence of geopolitical dynamics. While the UN and international law have been instrumental in resolving some conflicts, their success is not absolute, and their ability to enforce peace is contingent on various factors, including the willingness of powerful states to comply with international legal norms. This thesis affirms that while international law, under the UN's guidance, is a critical tool for global peace, its impact is limited by enforcement difficulties and the complex nature of international relations. Therefore, while international law is essential, it is not the sole factor in maintaining global peace; other elements, such as geopolitical strategies and power interests, also play crucial roles.